Pengaruh Fear of Missing Out, Brand Image, dan Discount Voucher terhadap Impulse Buying Konsumen Gen-Z pada Platform E-Commerce Shopee di Kecamatan Cigombong, Kabupaten Bogor - Kholifah, Novi Aulia; Nugraha, Muhammad Hadi Maulidin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to determine the influence of Fear of Missing Out (FOMO), Brand Image, and Discount Vouchers on Impulse Buying in Generation Z consumers who use the Shopee e-commerce platform in Cigombong District, Bogor Regency. The data source used in this study is primary data by distributing questionnaires, the population in this study is Generation Z consumers (born between 1997 and 2012) who actively use the Shopee e-commerce platform and are domiciled in Cigombong District, Bogor Regency. The selection of Gen-Z is based on their characteristics of being highly responsive to digital influence, promotions, and social trends. The phenomenon of Impulse Buying is increasingly relevant in the digital era, especially among Gen-Z who are heavily influenced by social media and online promotions. The study focuses on Shopee as one of the largest e-commerce platforms in Indonesia, given West Java's dominance in the e-commerce market share and Gen-Z's tendency towards impulse purchases. The sampling technique used non-probability sampling, the method used, namely purposive sampling with the lemeshow formula and obtained the minimum number of samples needed was 96 respondents, which was successfully fulfilled in this study. The analysis tool used is SPSS 27 software. The results of the study show that Fear of Missing Out, Brand Image, and Discount Voucher significantly have a positive effect on the Impulse Buying of Gen-Z consumers on the Shopee e-commerce platform in Cigombong District, Bogor Regency. Specifically, FoMO encourages impulse purchases due to the fear of missing out on trends, strong Brand Image increases spontaneous buying interest, and Discount Vouchers trigger immediate purchase decisions. The combined contribution of these three variables to Impulse Buying suggests that these factors are the main drivers of impulse buying behavior among Gen-Z Shopee users.